Echocardiographic probability of pulmonary hypertension according to the direct and indirect signs: a validation study. (14th October 2021) - D'Alto, M; Di Maio, M; Romeo, E; Argiento, P; Blasi, E; Di Vilio, A; Abbate, M; D'Andrea, A; Naeije, R; Golino, P
Abstract: Background: Transthoracic echocardiogram is the most important non-invasive screening tool for pulmonary hypertension (PH), but right heart catheterization (RHC) remains mandatory to establish the diagnosis. According to the current guidelines, the echocardiographic probability of PH is based on the combination of direct and indirect signs. In the 6th World Symposium on Pulmonary Hypertension, PH has been defined as mean pulmonary artery pressure (mPAP) >20 mmHg, and pulmonary vascular resistance (PVR) ≥3 WU. Aim: To validate the echocardiographic direct and indirect signs of PH suggested by the guidelines in view of the new definition of PH in patients who underwent echocardiography and RHC. Methods: All consecutive patients referred between January 2018 and December 2019 to undergo RHC for suspected PH were prospectively enrolled in the study. Echocardiography was performed within one hour from indicated RHC. Results: Overall, 263 patients were enrolled: 33 (13%) had normal pulmonary pressures, and 230 (87%) had PH. Among the 230 patients with PH, 136 (59%) had pre-capillary and 94 (41%) had post-capillary PH. All underwent echocardiography within one hour from RHC. At univariable logistic regression test, tricuspid regurgitant jet (TRJ) >2.9 m/sec [OR 8.32 (3.15–26.37, p<0.001)], left ventricle eccentricity index >1.1 [OR 5.57 (2.44–14.41, p<0.001)], right ventricle outflow tract acceleration time <105 msec [OR 4.90 (2.29–10.59, p<0.001)], pulmonary artery diameter >25 mm [OR 4.74 (2.01–13.09, p=0.001)], right-to-left ventricle basal diameter >1 [OR 4.54 (1.83–13.74, p=0.003)], and early diastolic pulmonary regurgitation velocity >2.2 m/sec [OR 3.14 (1.07–13.46, p=0.067)], predicted PH, whereas dilated inferior vena cava and right atrial area did not. At multivariable analysis, only TRJ >2.9 m/sec [OR 7.95 (2.78–27.07, p<0.001)] and left ventricle eccentricity index >1.1 [OR 4.89 (1.75–15.35, p=0.004)] showed a positive correlation to PH. The best area under the curve (AUC, 0.86) for predicting PH was obtained with TVR >2.9 m/sec + 2 indirect signs (sensitivity 0.77, specificity 0.94). Non-invasive estimate of mPAP showed a good correlation to invasive measurement (regression coefficient β 16.8±0.7, p<0.001 and R2 for the linear regression 0.68). The Bland–Altman analysis demonstrated low bias (−2.0 mmHg) and acceptable limits of agreement (upper limit +11.0 mmHg; lower −15.1 mmHg) between echocardiographic estimates and invasive measurement of mPAP (Figure 1). Conclusions: Echocardiographic direct and indirect signs of PH as suggested by the current guidelines should be used to assess the probability of PH being present. Echocardiographic measurements have high accuracy (low bias) and moderate precision (acceptable limits of agreement) The best area under the curve for predicting PH according to the new definition (mPAP >20 mmHg and PVR ≥3 WU) can be obtained with TVR >2.9 m/sec + 2 indirect signs. Funding Acknowledgement: Type of funding sources: None.